Data for Real-time water use data collected via automatic timers (n=336) installed in individual showers on the Cranfield campus - Nicklin, Harry; Jeffrey, Paul; Smith, Heather M. (Cranfield University, 2026)
Showering is among the most resource intensive activities in terms of household water and energy consumption. Reducing both water and associated energy consumption, which continues to be stubbornly high in many jurisdictions, calls for changes in behaviour. Using real-time data feeds via automatic shower timers (n=336) installed in individual showers on a university campus and providing five forms of messaging inspired by the COM-B behaviour change framework, we analysed the impacts of selected interventions on shower durations over a four-month experimental period.
Data was collected on shower duration from seven trial groups C = No shower timer 0 = Shower timer only 1 = Shower timer with time goal only 2 = Shower timer with time goal and water footprint message 3 = Shower timer with time goal and energy footprint message 4 = Shower timer with time goal and water saving tip 5 = Shower timer with time goal and group identity message
Keywords: Water use behaviour; showers; timer; messaging; student halls